2022
DOI: 10.26434/chemrxiv-2022-smm08
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrochemical Recycling of Adenosine Triphosphate in Biocatalytic Reaction Cascades

Abstract: Adenosine triphosphate (ATP) provides the driving force necessary for critical biological functions in all living organisms. In synthetic biocatalytic reactions, this cofactor is recycled in situ using high-energy stoichiometric reagents, an approach that generates waste and poses challenges with enzyme stability and downstream purification. On the other hand, electrons are a cheap and green source of energy. We report a method that uses electricity to turn over enzymes for ATP generation. The method is simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Recently, an alternative electrochemical method for ATP was described under air-free conditions that could be successfully implemented in this cascade to avoid the challenges of oxygen mass transfer. 83 ■ CURRENT STATE-OF-THE-ART Biocatalysis continues to be highly impactful for key synthetic challenges in the pharmaceutical industry. In all the industrial examples highlighted, there have been significant challenges to the implementation of biocatalytic transformations.…”
Section: ■ Multi-step Enzymatic Cascadesmentioning
confidence: 99%
“…Recently, an alternative electrochemical method for ATP was described under air-free conditions that could be successfully implemented in this cascade to avoid the challenges of oxygen mass transfer. 83 ■ CURRENT STATE-OF-THE-ART Biocatalysis continues to be highly impactful for key synthetic challenges in the pharmaceutical industry. In all the industrial examples highlighted, there have been significant challenges to the implementation of biocatalytic transformations.…”
Section: ■ Multi-step Enzymatic Cascadesmentioning
confidence: 99%
“…This process has now also been run on a 1 kg scale (Scheme 22b). 102 With these collective investments in electrochemistry, we are now well-equipped to apply this prospective investment to the company's portfolio when the opportunity arises.…”
Section: Current and Future Directions: Electrochemistry Base Metal C...mentioning
confidence: 99%
“…The Catalysis Laboratory demonstrated that this approach was feasible for the cofactor flavin adenine dinucleotide (FAD) for adenosine triphosphate (ATP) recycle and applied this capability to a biocatalytic cascade process for the glycosylation step in molnupiravir ( 80 ), eliminating the need for dioxygen or catalase. This process has now also been run on a 1 kg scale (Scheme b) . With these collective investments in electrochemistry, we are now well-equipped to apply this prospective investment to the company’s portfolio when the opportunity arises.…”
Section: Current and Future Directions: Electrochemistry Base Metal C...mentioning
confidence: 99%